Effects of sulphurous gases in two CO2 springs on total sulphur and thiols in acorns and oak seedlings (Atmospheric Environment, 2004)
Quercus ilex and Quercus pubescens acorns were collected at two CO2 springs in Tuscany (Bossoleto and Viterbo, resp.). In addition to elevated CO2, these springs are a source of H2S and SO2 . Acorns from a comparable ﬁeld site distant from CO2 springs were used as controls. Acorns from CO2 springs contained signiﬁcantly higher sulphur concentrations than controls (0.67 vs. 0.47 mg g 1 dw in Q. ilex cotyledons and 1.01 vs. 0.80 in Q. pubescens) and, in Q. ilex, also more glutathione (1634 vs. 1393 nmol g 1 dw). When acorns were germinated and seedlings grown under ambient air conditions in the Botanical Garden in Graz for one year, leaves of Q. pubescens grown from CO2 spring acorns showed signiﬁcantly higher S-concentrations than leaves grown from control acorns (2.27 mg g 1 vs. 1.56 mg g 1 dw), and those of Q. ilex higher glutathione concentrations (929 vs. 462 nmol g 1 dw, CO2 spring vs. control acorns). One-year-old Q. ilex seedlings grown from CO2 spring acorns also showed elevated rates of chromosomal aberrations in root tips (a widely used test for environmental impacts), suggesting a permanent stress situation of the seedlings originating from the CO2 springs.

Photosynthesis, Soluble and Structural Carbon Compounds in Two Mediterranean Oak Species (Quercus pubescens and Q. ilex) after Lifetime Growth at Naturally Elevated CO2 Concentrations (Plant Biology, 2001)
Abstract: To study physiological responses of mature forest trees to elevated CO2 after lifetime growth under elevated atmospheric CO2 concentrations (pCO2), photosynthesis, Rubisco content, foliar concentrations of soluble sugars and starch, sugar concentrations in transport tissues (phloem and xylem), structural biomass, and lignin in leaves and branches were investigated in 30- to 50-year-old Quercus pubescens and Q. ilex trees grown at two naturally elevated CO2 springs in Italy. Ribulose-1,5-bisphosphate carboxylase/oxygenase content was decreased in Q. pubescens grown under elevated CO2 concentrations, but not in Q. ilex. Photosynthesis was consistently higher in Q. pubescens grown at elevated CO2 as compared with “control” sites, whereas the response in Q. ilex was less pronounced. Stomatal conductance was lower in both species leading to decreased transpiration and increased instantaneous water use efficiency in Q. pubescens. Overall mean sugar + starch concentrations of the leaves were not affected by elevated pCO2, but phloem exudates contained higher concentrations of soluble sugars. This finding suggests increased transport to sinks. Qualitative changes in major carbon-bearing compounds, such as structural biomass and lignins, were only found in bark but not in other tissues. These results support the concept that the maintenance of increased rates of photosynthesis after long-term acclimation to elevated pCO2 provides a means of optimization of water relations under arid climatic conditions but does not cause an increase in aboveground carbon sequestration per unit of tissue in Mediterranean oak species.

Isotope discrimination and photosynthesis of vegetation growing in the Bossoleto CO 2 spring (Chemosphere, 1998)
The Bossoleto CO2 spring emits CO2 which has a stable carbon isotopic ratio (~5~3C = - 8%o). We determined ~3C on leaves of several individual species growing in Bossoleto and in a nearby control site at ambient CO,.. ~5t3C was 6% more negative in leaves of species collected from the grassland community of Bossoleto, indicating increased discrimination (A) against the heavy carbon isotope. No such changes were found in ruderal species growing in the same spring, suggesting that photosynthetic capacity was much less affected. A was substantially increased under elevated CO2 in leaves of Quercus pubescens but not in Quercus ilex, which also did not show any increase in non-structural carbohydrates. Gas-exchange measurements made on Plantago lanceolata, supported the view that photosynthetic capacity is decreased in plants grown under elevated CO: and on poor soils

Modifications of the leaf surface structures of Quercus ilex L. in open, naturally CO2-enriched environments (Plant, Cell & Environment, 1998)
Two Italian CO2 springs allowed us to study the long-term effect of a 350–2600 μmol mol–1 increase in CO2 concentrations on the surface structures of leaves of Quercus ilex L. Carbon dioxide increased the quantity of cuticular waxes, above an apparent threshold of 750 μmol mol–1 CO2. Leaf wettability was not modified by CO2 concentrations. Reduction in stomatal frequency was observable up to 750 μmol mol–1 CO2, the slope being almost the same as that estimated for the increase in CO2 concentration from pre-industrial times to the present. At higher concentrations, CO2 seemed to exert no more impact on stomatal frequency.

Photochemical response to summer drought in Quercus ilex trees growing in a naturally CO2 enriched site (IMPACTS OF GLOBAL CHANGE ON TREE PHYSIOLOGY AND FOREST ECOSYSTEMS, 1998)
The effect of the interaction between water stress and growth at elevated CO2 on the leaf photochemistry were studied in Quercus ilex trees, growing in a naturally CO2 enriched site (the Bossoleto, Italy). Those plants were compared with plants growing nearby in similar soils but at ambient CO2 concentration. Our data indicate that down-regulation of photosynthesis is lower in non-watered trees from the enriched site than in non-watered trees from the ambient-CO2 site This may be associated to the higher carbon availability for the consumption of the excess absorbed light energy or to an increased protection of the photochemical apparatus against oxidative stress in plants grown under elevated CO2.

Transpiration and stomatal behaviour of Quercus ilex plants during the summer in a Mediterranean carbon dioxide spring (Plant, Cell & Environment, 1998)
Variations in the water relations and stomatal response of Quercus ilex were analysed under field conditions by comparing trees at two locations in a Mediterranean environment during two consecutive summers (1993 and 1994). We used the heat-pulse velocity technique to estimate transpirational water use of trees during a 5 month period from June to November 1994. At the end of sap flow measurements, the trees were harvested, and the foliage and sapwood area measured. A distinct environmental gradient exists between the two sites with higher atmospheric CO2 concentrations in the proximity of a natural CO2 spring. Trees at the spring site have been growing for generations in elevated atmospheric CO2 concentrations. At both sites, maximum leaf conductance was related to predawn shoot water potential. The effects of water deficits on water relations and whole-plant transpiration during the summer drought were severe. Leaf conductance and water potential recovered after major rainfall in September to predrought values. Sap flow, leaf conductance and predawn water potential decreased in parallel with increases in hydraulic resistance, reaching a minimum in mid-summer. These relationships are in agreement with the hypothesis of the stomatal control of transpiration to prevent desiccation damage but also to avoid ‘runaway embolism’. Trees at the CO2 spring underwent less reduction in hydraulic resistance for a given value of predawn water potential. The decrease in leaf conductance caused by elevated CO2 was limited and tended to be less at high than at low atmospheric vapour pressure deficit. Mean (and diurnal) sap flux were consistently higher in the control site trees than in the CO2 spring trees. The degree of reduction in water use between the two sites varied among the summer periods. The control site trees had consistently higher sap flow at corresponding values of either sapwood cross-sectional area or foliage area. Larger trees displayed smaller differences than smaller trees, between the control and the CO2 spring trees. A strong association between foliage area and sapwood cross-sectional area was found in both the control and the CO2 spring trees, the latter supporting a smaller foliage area at the corresponding sapwood stem cross-sectional area. The specific leaf area (SLA) of the foliage was not influenced by site. The results are discussed in terms of the effects of elevated CO2 on plant water use at the organ and whole-tree scale.

Vulnerability of xylem to embolism in relation to plant hydraulic resistance in Quercus pubescens and Quercus ilex co-occurring in a Mediterranean coppice stand in central Italy (New Phytologist, 1998)
The seasonal patterns of xylem embolism and xylem transport properties in Quercus pubescens Willd. and Quercus ilex L. trees growing in a natural mixed coppice stand in conditions of severe water stress were investigated. Xylem embolism was evaluated in both dehydrating branches and in apical twigs during a whole year. Measurements of xylem water potential were conducted from predawn to sunset on selected sunny days. On the same days, diurnal courses of leaf conductance were monitored. Measurements of half-hourly sap flow were made by the heat-pulse technique throughout the summer. At the onset of summer, a sharp decrease in water potential was observed in both species. Full recovery of water potentials was observed for both species after the first major rainfall event in September. Both experienced serious embolism throughout the year, ranging between minima of c. 60% (expressed as percentage loss of hydraulic conductivity) after the rains in autumn and after bud burst in spring, and maxima of c. 80% during summer and after freezing-thawing events during the winter season. A significant negative linear relationship was found between water potential and xylem embolism in branches dehydrating in air for Q. pubescens and Q. ilex. Q. pubescens had greater efficiency in hydraulic transport (higher specific conductivity and leaf specific conductivity) by the xylem than Q. ilex. In June, leaf conductance was high early in the morning and decreased gradually during the day. Midday depression of leaf conductance, as a result of high evaporative demand combined with water deficit, was observed in both species. In August, leaf conductance of both species was greatly reduced, as water potential dropped to extremely low values, and the stomata were almost completely closed during the afternoon. No hysteresis resulting from plant capacitance was observed in the relationship between shoot water potential and sap flow. Q. pubescens exhibited very high values of whole-tree hydraulic resistance between July and September, whereas Q. ilex generally showed lower values. The effect of soil moisture depletion on the relationship between sap flow and shoot water potential appears as a lowering of water potential at zero flow. A significant decrease of whole-tree hydraulic resistance in both species was observed with the onset of the autumn, preceding the partial recovery of twig hydraulic conductivity. The results demonstrate that both Q. pubescens and Q. ilex, although highly tolerant of severe water stress and tissue dehydration, operate at the limits of safety which are surpassed under severe droughts, and prolonged climatic stress might predispose these Quercus species to decline.

Thirty years of in situ tree growth under elevated CO2: a model for future forest responses? (GLOBAL CHANGE BIOLOGY, 1997)
Rising concentrations of atmospheric carbon dioxide have been predicted to stimulate the growth of forest trees. However, long-term effects on trees growing to maturity and to canopy closure while exposed to elevated CO2 have never been examined. We compared tree ring chronologies of Mediterranean Quercus ilex which have been continuously exposed to elevated CO2 (around 650 mu mol mol(-1)) since they were seedlings, near two separate natural CO2 springs with those from trees at nearby ambient-CO2 `control' sites. Trees grown under high CO2 for 30 years (1964-93) showed a 12% greater final radial stem width than those growing at the ambient-CO2 control sites. However, this stimulation was largely due to responses when trees were young. By the time trees were 25-30 y old the annual difference in tree ring width between low and high CO2 grown trees had disappeared. At any given tree age, elevated CO2 had a relatively greater positive effect on tree ring width in years with a dry spring compared to years with more rainfall between April and May. This indicates a beneficial effect of elevated CO2 on tree water relations under drought stress. Our data suggest that the early regeneration phase of forest stands can be accelerated in CO2-enriched atmospheres and that maximum biomass per land area may be reached sooner than under lower CO2 concentrations. In our study, high CO2 grown Q. ilex trees reached the same stem basal area at the age of 26 y as control trees at 29 y,i.e. three years earlier (faster turnover of carbon?). Reliable predictions of the future development of forests need to account for the variable responses of trees over their entire lifetime. Such responses to elevated CO2 can presently only be assessed at such unique field sites.

Water relations of oak species growing in the natural CO2 spring of Rapolano (central Italy) (Ann. For. Sci., 1996)
The effect of elevated atmospheric carbon dioxide on water relations was examined on downy oak (Quercus pubescens) and holm oak (Q ilex) trees. The study was conducted on trees growing in a naturally enriched CO2 spring. Sap velocity and sap flow were measured by the heat pulse technique. On the same trees, daily courses of xylem water potential, leaf conductance and transpiration were monitored. Plant water relations were evaluated by pressure-volume analysis method on shoots; on the same branches, relative conductivity of xylem was measured. Both species exhibited increased osmotic potential and decreased symplasmic fraction of water in trees adapted to increased CO2. Downy oak showed lower stomatal conductance under elevated CO2, but holm oak did not. Both species displayed higher sap flow in control trees. In both species, increased carbon dioxide did not influence xylem embolism formation.

Leaf metabolism during summer drought in Quercus ilex trees with lifetime exposure to elevated CO2 (JOURNAL OF BIOGEOGRAPHY, 1995)
A marginal improvement in the response of Quercus ilex adult trees to drought appears to occur under a long-term natural CO2 enrichment. This is expressed, for example, by the absence of midday stomatal closure in trees growing under elevated CO2. Some protection against high irradiance and high temperature seems also to occur at the photochemical level, presumably as a result of more carbon available to the consumption of excess light energy. This would allow a better performance of the plants grown under elevated CO2 during the warmer hours of the day and therefore playing an important adaptation role under drought conditions. A marginal increase in the concentration of soluble sugars and starch was observed in the leaves of trees growing at elevated CO2 as compared with plants at ambient CO2, mainly during the midday hours. We may speculate that this will be advantageous both in terms of carbohydrate reserves for growth (e.g. more roots) and osmotic adjustment.
From Duplicate 2 (Leaf metabolism during summer drought in Quercus ilex trees with lifetime exposure to elevated CO2 - Chaves, M M; Pereira, J S; Cerasoli, S; CliftonBrown, J; Miglietta, F; Raschi, A)